Rheokinetics of Cement Paste Hydration during the Dormant Phase - Masalova Irina; Mbasha Willy; Haldenwang Rainer; Malkin Alexander Ya (Applied Rheology, 2018)
The hydration kinetics of four CEM I 52.5 N cements in the presence of two different superplasticizers was studied. The kinetics was characterized by monitoring the evolution of the dynamic modulus at constant frequency on a rotational rheometer. The method consists of predicting the time dependence of the elastic modulus by a kinetic equation of the self-acceleration type and fitting the equation to the experimental data. The model defines two main characteristic constants i.e. the characteristic time which defines the initial rate of hydration and the self-acceleration coefficient. It is shown that the model can accurately predict the initial hydration of cement paste with and without superplasticizer. The effect of the different cement properties and their interaction with superplasticizers can be observed in the kinetics of hydration.